Оцінка спектральної густини потужності на основі методу періодограми Уелча для когнітивного радіо - Кирик, М. І.; Янишин, В. Б.; Колодій, Р. С. (Видавництво Львівської політехніки, 2015)
Розглянуто методи сканування спектра для когнітивного радіо: оригінальний метод періодограми та метод періодограми Уелча як методи для виявлення енергії сигналу первинного користувача когнітивного радіо. Проведено докладний теоретичний аналіз кожного етапу роботи детектора енергії на базі періодограми Уелча. На основі цих даних створено імітаційну модель системи виявлення енергії для оцінки спектральної густини потужності під час роботи в каналі із сумішшю адитивного білого гауссівського шуму і QPSK маніпульованого сигналу. Проведено дослідження з різними вхідними параметрами: відношення сигнал-шум, кількістю елементів ШПФ та довжиною блоків для випадків з перекриттям і без перекриття сегментів. In this paper considered spectrum sensing methods for cognitive radio that based on energy detection. The periodogram method is a DFT based method to estimate power spectral density (PSD). The name of the periodogram comes from the fact that it was first used in determining possible hidden periodicities in time series. The analysis of statistical properties of the periodogram shows its poor quality as an estimator of the PSD. The bias and variance are often used as measures to characterize the performance of an estimator. The two effects caused by the bias of the estimate are smearing and leakage. The main limitations of the periodogram method yield from the variance. The periodogram is an inconsistent spectral estimator which means that it continues to fluctuate around the true PSD with a nonzero variance. This effect cannot be eliminated even if the length of the processed sample N increases without a bound. The idea of theWelch’s periodogram is to divide the data sequence into segments in order to reduce the large fluctuations of the periodogram. In the Welch’s method these data segments are also allowed to overlap, which is a feature that distinguishes it from some other modified periodograms. The simulation model works according to the following scheme. The primary user sends quadrature phase shift keying (QPSK) symbols on a 1 MHz frequency channel with the carrier frequency of 4 MHz over a complex additive white Gaussian noise (AWGN) channel. Symbols are sent at the symbol rate of 500 ksymbols/s. First, the noise has been added to the RF input signal. Then received signal has been downconverted to baseband. The Welch’s periodogram alerts when received signal energy exceeds the detection threshold. The simulations show that Welch’s periodogram signal detection method operates well for narrowband signals. Simulations confirm that Welch’s periodogram enhances the performance of the periodogram method. The main limitations of the periodogram method yield from the variance. The periodogram is an inconsistent spectral estimator which means that it continues to fluctuate around the true PSD with a nonzero variance. This effect cannot be eliminated even if the length of the processed sample increases without a bound. Furthermore, the fact that the periodogram values are uncorrelated for large number of the processed samples makes the periodogram exhibit an erratic behavior.
Power spectral density evaluation based on Welch’s periodogram for cognitive radio
Keywords: когнітивне радіо; сканування спектра; виявлення енергії; спектральна густина потужності; періодограма Уелча; cognitive radio; spectrum sensing; energy detection; power spectral density; Welch’s periodogram